ISU OTONOMI DAN TUNTUTAN PERUBAHAN PERAN SUMBER DAYA MANUSIA DALAM ORGANISASI PUBLIK - SUTANTO, DJOKO (Universitas Surakarta, 2012)
The role of human resource management in the administration of the country into a topic that has always attracted scientists in the study of public administration (Frederickson, 1997; Osborne and Plastrick, 2000), especially in recent years. Major changes that occurred in government organizations 90s that preceded the emergence of the phenomenon of autonomy, democratization, globalization, and the information technology revolution to impose a new requirement changes the role of the government apparatus that requires public organizations that are a radical transformation in the field of management. Government officials are not only required merely to be flexible and adapt to the highly dynamic mobile environment but also must be able to anticipate the various forms of change and proactively prepare the necessary changes. In realizing the need to support all of strategic plans and staffing system, which is aimed at creating new roles, new competencies and new ways to organize the government apparatus. Keywords: transformation of the role of human resources, the issue of autonomy, public organizations.